Modelamento 3D de pegmatito com uso de GPR, geoquímica e estatística multivariada: exemplo de um pegmatito do Distrito de Antônio Ferreira - Franciscópolis/MG - Henrique Chaves Joncew (2017)
A pegmatite-hosted tourmaline mine in the Antônio Ferreira District, Franciscópolis/MG, was the subject to a basic geologic modelling comprising topographic survey, Ground Penetrating Radar (GPR) profiling and Geochemical and Multivariate Statistical analyses. Situated in the core of the Araçuaí Orogen, the regions main lithological units are the Neoproterozoic metasedimentary Tumiritinga and São Tomé Formations, which are intruded by syn to late-tectonic Santa Rosa Granite and São Vitor Tonalite. Several granite-related pegmatite-hosted gem deposits are found throughout the Districts surroundings, thus making gem-mining an important activity for the local economy. Nevertheless, it is yet carried out under very rudimentary conditions of logistics, machinery and operation. Hence, the performed geological modelling aimed to assist creating a default research methodology for pegmatitic mineral deposits, ensuing gem-mining optimization in the future. GPR, though successfully applied by several branches of Geoscience, is an asset yet scarcely deployed on pegmatite exploration. However, during profiling radar proved itself an appropriate tool for detecting both rock contacts and anomalies within the pegmatite body which may correspond to mineralized gem pockets. Geochemical and Multivariate Statistical analyses, even with a lean space sample, were able to characterize the Antônio Ferreira pegmatite as lowly differentiated, and to point differences between the sampling points. Tourmalines from the mural zone and feldspars from the base contact distinguish themselves from the remaining minerals as anomalous geochemichal and statistical groups. This may hold connection to factors relative to the crystallization of these portions of the rock. Connecting these data to the topographic survey made it possible to create a computerized spatial reproduction of the mine and the pegmatite body with its structural anomalies. Therefore, the proposed methodological approach proved to be a valid alternative, which can be expanded into broader, more robust and extensive surveys for more fruitful and definitive results to guide gemstones prospecting in pegmatites.